2008
DOI: 10.1007/s11419-008-0061-y
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for detecting fenitrothion, its metabolite 3-methyl-4-nitrophenol, and other organophosphorus pesticides in human urine by LC-MS

Abstract: acute OP poisoning is most commonly encountered in emergency or forensic medicine [2,3]. The majority of such cases are attempts of suicide; in Japan, the OP compound most commonly used for this purpose is fenitrothion, followed by malathion and dichlorvos [4].Fenitrothion is categorized as a "moderately hazardous compound" (WHO class II) and is extensively used in many countries, including Japan, Canada, and Australia [3,5]. Although its oral toxicity in rats is low, fenitrothion poisoning is often life threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…Pattern of poisoning in Japan This result seems to be related to an aspect of Japanese culture, in which pesticides are chosen as a means of suicide [5]. This pattern is totally different from those in the UK, Germany, Iran, and Nordic countries [6][7][8][9], but similar to those reported in Greece, India, South Korea, and Uganda [10][11][12][13].…”
Section: Resultsmentioning
confidence: 59%
“…Pattern of poisoning in Japan This result seems to be related to an aspect of Japanese culture, in which pesticides are chosen as a means of suicide [5]. This pattern is totally different from those in the UK, Germany, Iran, and Nordic countries [6][7][8][9], but similar to those reported in Greece, India, South Korea, and Uganda [10][11][12][13].…”
Section: Resultsmentioning
confidence: 59%
“…3). These results significantly improved the separation speed from other methods that described in the literature (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(48)(49)(50). Table 2 further illustrates this achievement and compares how other analytical techniques such as GC, LC, and MEKC (long-end injection) performed with respect to the MEKC (short-end injection).…”
Section: Resultsmentioning
confidence: 71%
“…In GC analysis, they were commonly separated using GC‐mass spectrometry (MS) and GC with flame photometric detector (FPD) . In LC analysis, high‐performance liquid chromatography (HPLC) coupled with UV‐Vis (UV) detector and MS were commonly used.…”
mentioning
confidence: 99%
“…Analysis takes place in either positive (PI) or in negative (NI) ionization mode (Barcelo et al, 1993;Lacorte & Barcelo, 1995 (Barcelo et al, 1993;Lacorte & Barcelo, 1995). LC-MS instruments with APCI have been widely utilized for trace detection of OP levels in a range of samples from the environment (Ingelse et al, 2001;Schreiber et al, 2000;Slobodnik et al, 1996) to agriculture (Mol et al, 2003;Titato et al, 2007) and biological specimen (Inoue et al, 2009), due to APCI's lack of signal suppression from matrix components. Ingelse et al demonstrated APCI usefulness for detecting very polar OP pesticides in water (Ingelse et al, 2001).…”
Section: Ionization Sourcesmentioning
confidence: 99%